A novel use of social media to evaluate the occurrence of skin lesions affecting wild dusky grouper, Epinephelus marginatus (Lowe, 1834), in Libyan coastal waters. Issue 5 (15th August 2016) - Rizgalla, J; Shinn, A P; Ferguson, H W; Paladini, G; Jayasuriya, N S; Bron, J E
Abstract: The social media network Facebook ™ was used to gather information on the occurrence and geographical distribution of dusky grouper dermatitis, a skin lesion affecting the dusky grouper, Epinephelus marginatus . Dusky grouper are common targets for spear fishermen in the Mediterranean and by monitoring spearfishing activity in Libyan waters, it was possible to document skin lesions from their entries on Facebook. Thirty‐two Facebook accounts and 8 Facebook groups posting from 23 Libyan coastal cities provided a retrospective observational data set comprising a total of 382 images of dusky grouper caught by spearfishing between December 2011 and December 2015. Skin lesions were observable on 57/362 fish, for which images were of sufficient quality for analysis, giving a minimal prevalence for lesions of 15.75%. Only dusky grouper exceeding an estimated 40 cm total length exhibited lesions. The ability to collect useful data about the occurrence and geographical distribution of pathological conditions affecting wild fish using social media networks demonstrates their potential utility as a tool to support epidemiological studies and monitor the health of populations of aquatic animals. To our knowledge, this represents the first time that such an approach has been applied for assessing health in a wild population of fish.